Chemical and Toxicological Diagnosis of Acute Poisonings with Phenazepam - M. V. Belova; E. A. Klyuyev; E. S. Melnikov; D. M. Yeliseyeva (Неотложная медицинская помощь)
Background. The relative availability of Phenazepam makes it a frequent cause of overdose, suicide and non-medical use. At the same time, it remains insufficiently studied in chemical and toxicological terms.The aim of study. to create an accessible, rapid method for detecting Phenazepam in biological matrices of patients with acute poisoning.Materials and methods. We used thin-layer chromatography (TLC), gas chromatography with a mass selective detector (GC-MS), high performance liquid chromatography with a tandem mass-selective detector (LC-MS/MS) and immunochromatographic analysis (ICA). The preparation of samples of intact urine with the addition of standard solutions of Phenazepam and real urine samples of patients with acute poisoning with Phenazepam was carried out using liquid-liquid extraction or precipitation of related components of the sample with acetonitrile. Hydrolysis and derivatization were also added in GC-MS analysis.Results. The analysis of statistics of the Department of Acute Poisonings of the N.V. Sklifosovsky Research Institute for Emergency Medicine in 2014-2016 showed that Phenazepam poisonings averaged 9.2% of the total number of admissions and mainly occurred as suicidal attempts. A technique has been developed for the detection of Phenazepam by TLC, which gives more objective results than ICA. For confirmatory analysis, it is advisable to use LC-MS/MS method for the native substance and GC-MS for the products of hydrolysis after derivatization. Compared to confirmatory methods, the developed TLC-screening technique is expressive, does not require the use of expensive high-tech equipment, difficult sample preparation, and makes it possible to reliably detect toxic and lethal concentrations of Phenazepam.